MODEL PENGEMBANGAN KEMITRAAN PENDIDIKAN NON FORMAL DAN INFORMAL DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MEMBERDAYAKAN MASYARAKAT - Lesi Oktiwanti; Adang Danial; H Syaefuddin (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2017)
Abstract: This study aims to determine the development of the Partnership Non-Formal Education and Informal Corporate Social Responsibility (CSR) in Empowering Communities conducted in Program